The impact of social media on the development of student knowledge in Indonesia - Fitriana Fitriana; Irin Ramdhani; Wardina Suwedy; Yan Hermansyah; Arif Fuddin Usman (PINISI Discretion Review, 2023)
In the digital era, social media's pervasive influence on various aspects of life has become a focal point of academic inquiry, particularly in Indonesia, where its usage among students has seen a significant surge. This study aims to explore the impact of social media on the development of student knowledge in Indonesia, utilizing a qualitative research approach to delve into nuanced perspectives and experiences. The methodology involves in-depth interviews and focus group discussions with students from diverse educational backgrounds across Indonesia, alongside content analysis of their social media interactions. The findings reveal a dual-edged nature of social media's impact: on one hand, it serves as a dynamic platform for information exchange and learning enhancement, offering students access to a plethora of educational resources and peer-support networks. On the other hand, it poses challenges such as misinformation, distraction, and cognitive overload, which can impede knowledge acquisition and critical thinking. The study underscores the need for a balanced approach in leveraging social media for educational purposes, advocating for digital literacy programs to equip students with skills to critically assess and effectively utilize online information for their academic and personal growth.